Origin and interpretation of cancer transcriptome profiling: the essential role of the stroma in determining prognosis and drug resistance - Nicolas Goossens; Yujin Hoshida; Julio A Aguirre‐Ghiso (EMBO Molecular Medicine)
Abstract Mesenchymal gene expression in tumors has been implicated in cancer recurrence, metastasis, and poor prognosis of patients. The source of these mesenchymal signals has been mostly attributed to the epithelial‐to‐mesenchymal transition‐like phenotype of epithelial tumor cells. However, recent evidence from colorectal and other cancer transcriptome studies clearly shows that the mesenchymal gene expression likely originates from stromal cells in and around the tumor and that this microenvironment specifically confers tumor aggressiveness. These findings highlight the need to move away from tumor‐centric interpretations and to better establish the complementary role of the stromal microenvironment in fueling aggressive traits of cancer cells. This observation also suggests that future attempts at transcriptome profiling of whole tumor tissue must take into account the origin of mesenchymal gene expression profiles to better guide development of diagnostic and therapeutic strategies for cancer.